Analysis and Synthesis of Delta Operator Systems with Actuator Saturation - Yang, Hongjiu; Xia, Yuanqing; Geng, Qing (Studies in Systems, Decision and Control, 2019)
This book presents basic research on delta operator systems (DOS) with actuator saturation. It proposes null controllable regions of delta operator systems, introduces the enlarging of the domain of attraction and analyzes the performance of DOSs subject to actuator saturation. It also discusses the domain of attraction on different systems in delta domain, and investigates the applications in complicated systems using delta operator approaches.